A Decade of Experience with Drilled Foundations in Honolulu - James W. Niehoff (Deep Foundations Institute, 2016)
"Prior to 2003, most high rise structures in Honolulu, Hawaii were supported on driven pile foundations, extending through shallow coral strata and bearing in competent formations at depths of 100 ft (30 m) or greater. In 2003, the 40-story Hokua Tower became the first building in Hawaii to use continuous flight auger (CFA) piles for support. These piles derived most of their capacity from side shear in the shallow coral formations, which reduced their required lengths to less than 100 ft (30 m) sand significantly increased their capacity. Not only did CFA piles prove to be more efficient and cost-effective than driven piles, but the reduced noise and vibration associated with their installation made them and drilled piers the foundations of choice for most mid- to high-rise projects going forward. Because drilled foundations were new to Hawaii, it was necessary to develop effective design parameters for the unique soil and rock conditions found within this urban area. While drilled foundations were found to have many advantages over driven piles, construction techniques had to be modified to compensate for extensive voids in the coral formations. This paper presents a compendium of the data derived from numerous full scale, instrumented load tests conducted during the past decade and provides guidance for the design and installation of CFA and drilled pier foundation systems in areas having geologic settings and history similar to that of Honolulu.INTRODUCTIONThe State of Hawaii is one of the most remote areas in the world, lying nearly 2400 miles (3800 km) from the nearest continental land mass. In spite of this vast distance, the population of the islands has grown to over 1 million people, the majority of whom live within and in close proximity to the City of Honolulu on the Island of Oahu. The city is densely populated with over 400 high rise apartments, condominiums, hotels and office buildings located within 5 miles (8 km) of the city center (Fig.1). Nearly all of these buildings have been constructed within the past 50 years."